A novel supersaturated medium entropy alloy with superior tensile properties and corrosion resistance. (September 2020) - Fu, Ao; Liu, Bin; Lu, Wenjun; Liu, Bo; Li, Jia; Fang, Qihong; Li, Zhiming; Liu, Yong
Abstract: We introduce a novel stainless equiatomic FeCrNi medium entropy alloy (MEA) with improved tensile properties and corrosion resistance. This alloy exhibits superior tensile properties with yield strength of 644 MPa, ultimate tensile strength of ~1.03 GPa and ductility of ~54 %, mainly owing to the multiple deformation mechanisms including nanotwinning, deformation induced phase transformation and solution strengthening of intersitial elements. The high content of Cr in this alloy stimulates the formation of stable passivation film, resulting in a superior corrosion resistance. This work provides a guideline for the development of high-performance stainless materials via innovative composition design and processing techniques. Graphical abstract: Image, graphical abstract